2015
DOI: 10.1038/nmeth.3405
|View full text |Cite
|
Sign up to set email alerts
|

In vivo single-cell labeling by confined primed conversion

Abstract: Spatially confined green-to-red photoconversion of fluorescent proteins with high-power, pulsed laser illumination is negligible, thus precluding optical selection of single cells in vivo. We report primed conversion, in which low-power, dual-wavelength, continuous-wave illumination results in pronounced photoconversion. With a straightforward addition to a conventional confocal microscope, we show confined primed conversion in living zebrafish and reveal the complex anatomy of individual neurons packed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(117 citation statements)
references
References 34 publications
7
106
0
4
Order By: Relevance
“…To limit excitation in the Z-plane, we attempted to use a two-photon system. However, we observed that Dendra2 photoconversion did not occur under a two-photon regime, consistent with other reports (Dempsey et al, 2015). …”
Section: Resultssupporting
confidence: 93%
“…To limit excitation in the Z-plane, we attempted to use a two-photon system. However, we observed that Dendra2 photoconversion did not occur under a two-photon regime, consistent with other reports (Dempsey et al, 2015). …”
Section: Resultssupporting
confidence: 93%
“…Spatiotemporal quantitative imaging in vivo is not merely limited to early embryonic development but can also be exploited as a tool to study development and regeneration in whole organisms with potential benefits for future biomedical applications (Dempsey et al, 2012a(Dempsey et al, , 2015. The additional information acquired using these quantitative imaging techniques is critical for our understanding of the regulation of developmental processes in healthy and diseased states such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, until recently, spatially confined photoconversion using high-power, pulsed laser illumination was extremely inefficient. Now, Dempsey and colleagues have reported a unique optical mechanism, termed primed conversion, where dual-wavelength continuous-wave illumination results in pronounced photoconversion of fluorescent proteins (Dempsey et al, 2015). Confined primed conversion can be implemented on a conventional confocal microscope and succeeds in precise targeting of single cells in complex 3D structures.…”
Section: Quantitative Imaging Of Transcription Factor Dynamicsmentioning
confidence: 99%
“…After tail flick imaging, zebrafish were kept overnight at 28°C within the 96-well plate. At 2 dpf, zebrafish injected with the spinal cord neuron expressing GFE construct were anesthetized with 0.015–0.03% MS-222 (Argent Laboratories), embedded in 1–1.5% SeaPlaque agarose within a 30X Danieau’s solution (17.4 mM NaCl, 0.21 mM KCl, 0.12 mM MgSO 4 , 0.18 mM Ca(NO 3 ) 2 , 1.5 mM HEPES), and imaged using a Plan Apochromat ×20 objective on a commercial LSM 700 confocal microscope (Carl Zeiss AG), as similarly described 45 . Mosaic-labeled GFP positive cells were visualized throughout the zebrafish spinal cord using the tiled confocal stack feature of the microscope.…”
Section: Methodsmentioning
confidence: 99%